2020
DOI: 10.1016/j.ebiom.2020.102923
|View full text |Cite
|
Sign up to set email alerts
|

Molecular correlates of sensitivity to PARP inhibition beyond homologous recombination deficiency in pre-clinical models of colorectal cancer point to wild-type TP53 activity

Abstract: Background PARP inhibitors are active in various tumour types beyond BRCA -mutant cancers, but their activity and molecular correlates in colorectal cancer (CRC) are not well studied. Methods Mutations and genome-wide mutational patterns associated with homologous recombination deficiency (HRD) were investigated in 255 primary CRCs with whole-exome sequencing and/or DNA copy number data. Efficacy of five PARP inhibitors and their molecular cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 56 publications
1
28
0
Order By: Relevance
“…The results suggest that the PARPi signatures might be independent of the HRD signature. In line with this, recent studies support the expansion of PARP-targeted therapy in cancer irrespective of classical HRD signatures [5][6][7]. Next, we applied PARPis sensitivity and resistance gene signatures to both cancer cell lines and patient samples to identify cancer subtypes that are potentially vulnerable to PARPi.…”
Section: Reproductivity Of the Established Parpi Sensitivity And Resistance Gene Signaturesmentioning
confidence: 57%
See 2 more Smart Citations
“…The results suggest that the PARPi signatures might be independent of the HRD signature. In line with this, recent studies support the expansion of PARP-targeted therapy in cancer irrespective of classical HRD signatures [5][6][7]. Next, we applied PARPis sensitivity and resistance gene signatures to both cancer cell lines and patient samples to identify cancer subtypes that are potentially vulnerable to PARPi.…”
Section: Reproductivity Of the Established Parpi Sensitivity And Resistance Gene Signaturesmentioning
confidence: 57%
“…McGrail et al [23] used gene expression profiles from ovarian and breast cancer cell lines that display high sensitivity to olaparib and rucaparib, leading to deriving a transcriptional algorithm that can improve the prediction sensitivity to PARP inhibitors. In line with this, recent studies support the expansion of PARP-targeted therapy in cancer irrespective of classical HRD signatures [5][6][7]. In a recent phase III clinical trial recruiting patients with newly diagnosed advanced ovarian cancer who had a response to platinum-based chemotherapy, the therapeutic benefits from PARPi niraparib is regardless of the presence or absence of HRD [5].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Thus, metformin inhibits cancer cell growth and survival in both p53-dependent and p53-independent ways. Smeby et al showed that talazoparib, another PARPi, increases the number of TP53-positive nuclei in p53 WT cells, suggesting that the response to PARPis may provide a link between wild-type TP53 and HR deficiency, connected with RAD51 [ 67 ]. However, long-term (five days) treatment with 5 μM olaparib downregulates p53 in the p53 MUT ovarian cancer cell line OVCAR-3, whereas in the p53 WT cell line A2780, it upregulates p53 expression [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, in vitro studies have shown a synergistic effect of Olaparib and 5-FU in MSI-H CRC [272], whereas Olaparib monotherapy showed benefits in MSS CRC with non-functional HR, and was proposed as maintenance therapy in patients responsive to oxaliplatin-based regimens [273]. The enrichment of PARPi sensitive MSS cell lines was observed in those with preserved TP53 function and TP53-mediated suppression of RAD51 was appointed as a possible mechanism of action [274]. Further, data from 99 MSS CRC cell lines revealed that functionality of HR repair determined in the RAD51 assay could discriminate for PARPi susceptible CRC tumors, in which no increase in the percentage of RAD51 foci positive nuclei was observed upon radiation [273].…”
Section: Molecular Selection Of Crc Patients For Clinical Trials With Ddr Inhibitorsmentioning
confidence: 99%